2022
DOI: 10.1177/14673584221089747
|View full text |Cite
|
Sign up to set email alerts
|

Cultural heritage and tourism. A comparison of two destinations in Southern Moravia

Abstract: This paper addresses the question: why do two destinations with extremely valuable cultural heritage gain attractions have completely different tourism traffic results? The main aim of this paper was to find the various causes of this inequality. The comparative method was used and Lednice and Dolní Kounice in Southern Moravia were selected as case studies. Statistical data and strategic documents on regional and local levels were analysed. The study showed significant differences in the strategic conceptual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Heritage management processes can rely on a variety of managerial factors (e.g., resource allocation, strategic management tools) (e.g., [47][48][49]), as well as on social factors (e.g., value emphasis, tourist participation) (e.g., [50][51][52]). Modern projective programming and mapping technologies are also increasingly used [51,53].…”
Section: Caring For Heritagementioning
confidence: 99%
See 3 more Smart Citations
“…Heritage management processes can rely on a variety of managerial factors (e.g., resource allocation, strategic management tools) (e.g., [47][48][49]), as well as on social factors (e.g., value emphasis, tourist participation) (e.g., [50][51][52]). Modern projective programming and mapping technologies are also increasingly used [51,53].…”
Section: Caring For Heritagementioning
confidence: 99%
“…[48]) or its extended version TOWS/SWOT. M. Št'astná and A. Vaishar [49] attempted to answer the question: why do two destinations with extremely valuable cultural heritage obtain completely different results in terms of tourism? Their study revealed significant differences in strategic planning.…”
Section: Caring For Heritagementioning
confidence: 99%
See 2 more Smart Citations